Subungual glomus tumor in the little finger and use of diagnostic ultrasound: A case report - Lazo Vera, Jorge (2021)
We present the case of a 50-year-old patient who reported chronic pain under the nail of the little finger for five years, with no trauma history and which restricted his work activity. The glomus tumor is a benign neoplasm characterized by an acute and circumscribed pain in the subungual region that increases with pressure and cold, which are objective symptoms to suspect this condition. The highest incidence of glomus tumors occurs in adults; however, as it is infrequent, delayed diagnosis is common. The diagnosis must include imaging scans, especially ultrasound, which are an excellent and very accessible alternative in different populations. In our case, the tumor was clearly observed on the ultrasound images, which was crucial to choose the surgical excision as treatment. The anatomopathological evaluation revealed a glomus tumor and the subsequent relief of symptoms were confirmed after the surgery.